Performance Analysis of Solar operated BLDC motor - K. Sushita, Dr. N. Shanmugasundaram (International Journal of Advanced Science and Technology, 2020)
This Brushless DC (BLDC) motor is now a days in a variety of industrial applications due to its high performance, strong dynamic response, good reliability, and easy build. The motor is operated here is used using a photovoltaic array (PV) as solar energy is seen as the most promising source of renewable energy. The PV array is provided with constant solar radiation as input. The maximum power by which PV is generated to operate at maximum efficiency is tracked by the maximum power point tracking (MPPT) method. The incremental conductance MPPT algorithm is used here. The boost converter is used to increase the voltage as required. The three-phase six step inverter is used as an electronic commutator to operate a 1KW, 500V, 3000 rpm BLDC motor and analyze its stator current, stator emf, hall signal, rotor speed, and electromagnetic torque. The Performance is analyzed using Matlab / Simulink.